Analysis Large Language Model (LLM) for Digital Transformation in a Ministry - Andre Pratama Adiwijaya (International Journal Science and Technology, 2025)
Digital transformation in government requires the use of cutting-edge technology to improve efficiency and accuracy in decision-making. Ministries are strategic institutions that manage large-scale data and information, particularly related to regional government administration and population affairs. This article examines the application of Large Language Models (LLM) as an artificial intelligence (AI)-based solution to assist document processing, information extraction, and policy analysis. The study presents a relevant legal framework, LLM model recommendations, a schematic diagram of LLM implementation from end-to-end, and Python code examples for technical simulations. This approach is expected to strengthen the Ministry's digital system in accordance with the guidelines of the Electronic-Based Government System (SPBE) and One Data Indonesia.